Recommendations for altitude training programming to preserve athletes` health after COVID-19 pandemic - Manferdelli, G.; Bishop, D.; Franchi, M. V.; Sarto, F.; Girard, O.; Porcelli, S. (British Journal of Sports Medicine, 2020)
Low-to-moderate altitude (2000-2500m) training camps are an integral part of many athletes' training programs. Despite potential positive effects on performance, sojourning at altitude represents an important stress on the human body, with transiently increased pulmonary and kidney stress, neuroendocrine dysregulation, and immune perturbations. This highlights the importance of careful planning and organisation, which may be more critical during the current COVID-19 pandemic. Preliminary reports suggest that hypoxaemia and inflammation induced by COVID-19 result in heterogenous lung injury and acute respiratory distress syndrome, eventually leading to acute respiratory failure. Some authors have also speculated that COVID-19-induced acute respiratory distress syndrome may share some similarities with high-altitude pulmonary oedema. Even though COVID-19 is primarily a respiratory disease, it can also negatively affect the cardiovascular system, exposing affected patients to myocarditis or myocardial damage. Moreover, COVID-19 may impair renal function as well as the circulatory and the immune system.